Вы находитесь на странице: 1из 35

.

2004

517.2

. .-. , ..

: . / .-. .. ,
.. . . . , 2004. 40.
,

. .
.
1-
.
517.2


, 2004
., ..
2004

, .

,

, .
.
- .
1.
. F ( x )
f ( x)

x ,

F ( x ) x F ( x ) = f ( x )
.
.
F ( x ) = sin x

f ( x ) = cos x

x ( ,+) ,

(sin x ) = cos x x ( ,+) .


F ( x ) = arcsin x

( arcsin x ) =

f ( x ) =

1
1 x2

1
1 x2

x ( 1, 1) ,

x .

2.
1. F ( x )
C ,

f ( x) ,

F ( x ) + C ,

f ( x) .

. F ( x )
F ( x ) = f ( x ) .
F ( x) +

f ( x) ,

( F ( x ) + C ) = F ( x ) + C = f ( x ) + 0 = f ( x ) ,

f ( x) .

F2

2.

F1 (x )


(
x)

f ( x) ,

F 2 ( x ) F1 ( x ) .
. , :

F1 ( x ) = f ( x )

F2 ( x ) = f ( x ) x .

( F ( x) F ( x) ) = F ( x) F ( x) = f ( x) f ( x) = 0 .

F2 ( x ) F1 ( x ) = C

.
1 2 ,
F ( x ) ,

f ( x )

f ( x )

.
3. F ( x )

f ( x)

( x )

, ( x ) , F ( ( x ) )
f ( ( x ) ) ( x ) .

. : F ( x ) = f ( x ) .
F ( u ) ,

u = ( x ) :

( F ( ( x ) ) x = ( F ( u ) ) x = F u ( u ) u x ( x ) = f ( u ) u x ( x ) = f ( ( x ) ) ( x ).
, F (( x ) )
f ( ( x ) ( x ) .
3.
.

f ( x)

.
1 2 ,

f ( x)

. : f ( x ) dx = F ( x ) + C , F ( x )

f ( x) ,

C ,
f ( x)

f ( x )dx

, x .

.
sin xdx =cos x +C ,
sin xcos xdx =

( cos x ) =sin x

sin 2 x
sin 2 x
+C ,
=sin x cos x,
2
2

cos 2 x
cos 2 x
sin x cos x dx = 2 +C , 2 = sin x cos x.

sin 2 x
2

cos 2 x
:
2

sin 2 x cos 2 x 1

= .
2
2 2

f ( x)


.
4.
1)

: ( f ( x )dx ) x

( f ( x ) dx )

2)

f ( x )dx = F ( x ) + C ,

= f ( x) .

F ( x ) = f ( x ),

= ( F ( x ) + C ) = F ( x ) + C = f ( x ) .

: d f ( x )dx = f ( x )dx.
.

d f ( x )dx = ( f ( x )dx ) dx = f ( x )dx ,

3)
: F ( x ) dx = F ( x ) + C .
. F ( x ) = f ( x ) . f ( x )dx = F ( x ) + C ,

F ( x ) dx = F ( x ) + C .
,
:
F ( x ) + C = F ( x ) dx .

4)
:

dF ( x ) = F ( x ) + C .
.

dF ( x ) = F ( x ) dx ,

3.
5.
1.
:

( f ( x ) + g ( x ) )dx = f ( x )dx + g ( x )dx

(1)

. F ( x )

f ( x ) dx = F ( x ) + C1

g( x) .

f ( x)

g ( x ) dx = G( x ) + C 2 .

f ( x ) dx + g ( x ) dx = F ( x ) + G ( x ) + C ,

(2)

C = C1 + C 2 .
3

F ( x ) + G ( x ) + C = ( F ( x ) + G ( x ) ) dx.

F ( x ) = f ( x ) G ( x ) = g ( x ) ,
6

G( x )

F ( x ) + G ( x ) + C = ( f ( x ) + g ( x ) ) dx.

(3)

(2) (3), ( f ( x ) + g ( x ) )dx = f ( x )dx + g ( x )dx.

2.

: af ( x )dx = a f ( x )dx ,
(4)
a .
.

f ( x )dx = F ( x ) + C

F ( x)

f ( x) .

C1 .

a :
a f ( x ) dx = aF ( x ) + C ,

(5)

C = aC1 .
3 :

aF ( x ) +C = ( aF ( x ) ) dx.

( aF ( x ) ) = aF ( x )
,

F ( x ) = f ( x ),

( aF ( x ) ) = af ( x ).

aF ( x ) + C = af ( x ) dx

(6)

(5) (6) : af ( x )dx = a f ( x )dx.


(1) (4)
.

af ( x ) + bg ( x )

f ( x)

g( x)

, a b .

f ( x)

g( x)

c a b .

1 2 ,

:

( af ( x ) + bg ( x ) ) dx = a f ( x ) dx + b g ( x ) dx .


. n f1 ( x ), f 2 ( x ), , f n ( x ) a1 , a 2 , , a n
:

( a1 f1 ( x ) + a2 f 2 ( x ) + + an f n ( x ) )dx = a1 f1 ( x )dx + a2 f 2 ( x )dx + + an f n ( x )dx.



n
n

a
f
(
x
)

dx
=
ai f i ( x ) dx.

i =1 i i
i =1

6.
1. 0dx =C.

6. cos xdx =sin x +C.

x +1

dx

2. x dx = +1 + C , 1.
3.

7. 2 = tgx + C.
cos x
dx

dx
= ln x + C.
x

8. 2 = ctgx + C.
sin x

ax

9.

+ C , a > 0, a 1 ,
4. a x dx =
ln a

dx
1 x2

= arcsin x + C = arccos x + C1 .

dx = e x + C

dx

= arctgx + C = arcctgx + C1 .
10.
1+ x2

5. sin x dx =cos x +C.


C , C1 .



.
,

x +1
1
1
+1

=
( +1) x = x
+1 = +1 x

+
1

x +1
+1

x +1

: x dx = +1 + C , 1.
1

3 : x dx = ln x
8

+C.

,
ln x,
ln x =
ln ( x ),

x > 0,

x < 0.

( ln x ) ,
( ln x ) =

( ln ( x ) ),

x > 0,
x < 0.

1
x > 0 ( ln x ) = .
x

( ln( x ) ) =

1
( x ) = 1 ( 1) = 1 .
x
x
x

1
, (ln x ) = x

x 0 . , ln x

1
.
x


3.
7.
f ( x )dx.
.

x = ( t )

x = ( t ) .

( t ) ,

f ( x )dx = f ((t ))(t )dt.


.
: F ( x )

f ( x) ,

F (( t ) )

f (( t ) ) ( t ) . ,

: f (( t ) )(t )dt = F (( t ) ) +C

f (( t ) )( t )dt = F ( x ) +C

(1)


F ( x ) + C = f ( x )dx

F ( x ) + C = F ( x )dx

(2)

(1) (2) , f ( x )dx = f ((t ))(t )dt ,

x = ( t ) .

.
1)
9

f ( x )dx = F ( x ) +C , f ( ax + b ) dx = F ( ax + b ) + C ,
a
f ( ax +b )dx .
ax + b = t .

1
xt =
a

x=

t b
,
a

a 0.

f ( ax + b ) dx = f ( t ) a dt = a f ( t ) dt = a F ( t ) + C = a F ( ax + b ) + C.
,
1 ( ax + b )

( ax + b ) dx =

+1

dx

+1

+C,

1,

ax + b = a ln ax + b + C ,
1

sin ( ax + b ) dx = a cos( ax + b ) + C ,
1

cos( ax + b ) dx = 2 sin ( ax + b ) + C ,
e

ax +b

dx =

1 ax +b
e
+ C.
a

2)

dx
2

a x2

a 0.

x = at , xt = a

dx
2

a x

t=

adt
2

a a t

x
,
a

3)

2 2

a 1 t

dx
a2 x2
dx
x2 +m

x + x2 + m = t

, xt =

adt

= arcsin

dt
1 t 2

= arcsin t + C .

x
+ C.
a

m .

( ).

1 t2 + m
.
2 t2
10

x=

t2 m
2t

x2 + m = t x = t

t2 m t2 + m
=
,
2t
2t

1
t 2 +m
1
= 2

dt = dt = ln t +C.
2
2
t
t +m
2t
x +m
2t
dx

dx

x +m

=ln x + x 2 +m +C .

dx

4) 2 2 , a 0 .
x +a
x = at , xt = a
dx

adt

x 2 + a 2 = a 2t 2 +a 2

t=

x
,
a

1
dt
1
= arctg t + C.

2
a t +1 a

dx

2 2 = arctg + C.
a
a
x +a

5)

f ( x )

f ( x ) dx (

).

f ( x) = t .

f ( x )

dt

f ( x ) dx = t

f ( x ) dx = dt

=ln t +C =ln f ( x ) +C ,

f ( x )

f ( x ) dx = ln f ( x ) + C.
,
sin x
( cos x )dx = ln cos x +C ,
dx =
cos x
cos x
( sin x ) dx = ln sin x +C.
cos x
ctgxdx
=
dx
=

sin x
sin x

tgxdx =

8.
.

u( x )

v( x )

, u ( x )v( x )dx =u ( x )v( x ) u ( x ) v( x )dx.

11

.
(u ( x )v( x ) ) = u( x )v( x ) +u ( x ) v( x ).
, u ( x ) v( x ) = (u ( x ) v( x ) ) u( x ) v( x )

u ( x ) v( x )dx =(u ( x ) v( x )) dx u ( x ) v( x )dx .

(u ( x ) v( x ))dx =u ( x )v( x ) +C .
u ( x ) v( x )dx =u ( x )v( x ) +C u ( x )v( x )dx.
C
, u ( x )v( x )dx
,
.
.
v( x ) = dv( x ) u ( x ) dx = du ( x ) ,
u ( x )dv( x ) =u ( x )v( x ) v( x )du ( x )
: udv =uv vdu .
.
1) x nl x dx,
.

n =1

u = x ,

dv = l x dx ,


du = dx ,

( )

xl

dx = xl x l x dx = xl x l x + C = ( x 1) l x + C

n = 2

u = x 2 , dv = l x dx

(1)

du = 2xdx, v = l x

l dx = x 2l x 2 xl x dx

2 x

(2)

(1) (2) ,

2 x

l dx = x 2l x 2 xl x + 2l x + C = x 2 2 x + 2 l x + C

n = 3

u = x 3 , dv = l x dx

l dx = x 3l x 3 x 2l x dx

3 x

(3)

u = 3x 2 dx , v = l x

(4)

12

v =l x

(3) (4) , x 3l x dx = ( x 3 3x 2 6 x 6 ) l x + C .

n =4, 5, .

2) x n sin xdx

, , x 2 cos xdx.

cos x dx.
u = x 2 , dv = cos x dx ,

du = 2 xdx d v = sin x . x 2 cos xdx = x 2 sin x 2 x sin xdx.

u = x ,

dv = sin x dx ,

du = dx v = cos x .

x sin xdx = cos x ( cos x )dx = x cos x + sin x + C

cos xdx = x 2 sin x 2( x cos x + sin x + C ) = x 2 sin x + 2 x cos x 2 sin x + C.

u =ln x,

dv = x dx,

du =

dx
x

v=

x ln xdx,

3)

x +1
.
+1

x
=

ln xdx =

x +1
x +1 dx
x +1
1
ln x
=
ln x
x dx =

+1
+1 x
+1
+1

x +1
x +1
ln x
+C.
+1
( +1) 2

x ln xdx =

x +1
1

ln x
+ C , 1 .

+1
+1

ln xdx = x( ln x 1) +C.
4) arctgxdx .
dx
v =x.
u = arctgx , dv = dx , du =
2
1+ x

arctgxdx = xarctgx

x
dx .
1 + x2

x
1 1 + x2
1
1
dx
=
dx = ln 1 + x 2 + C = ln 1 + x 2 + C ,
1 + x2

2
2 1+ x
2
2

1 + x 2 > 0x.

1
, arctgxdx = xarctg ln (1 + x 2 ) + C.
2

5) arcsin xdx.
13

=0 :

u arcsin x , dv = dx ,

du =

arcsin xdx = x arcsin x

1 x 2 = t.

x 2 =1 t 2

x
1 x

1 x2

dx
1 x2

dx.

v = x.

2 xdx = 2tdt .

dx =

tdt
= t + C = 1 x 2 + C.
t

, arcsin xdx = x arcsin x +

1 x 2 +C.

9.
,
.
.
P( x )

: R( x ) = Q( x ) , P( x )

Q( x )

x .
.

-
, ( ) - 1A

2- ( ( x a ) k , A a ,
k

Mx + N
, M
x + px + q l
2

, N , p , q , l

p2
q < 0 ).
4


,

- 1- 2- .
) -
14

P( x) = a0 x n + a1 x n 1 + + an 1 x + an .

P( x )dx = (a0 x + a1 x + + an 1 x + an )dx =


= a0 x n dx + a1 x n 1dx + + an 1 xdx + an dx =
n

= a0

n 1

x n +1
xn
x2
+ a1
+ + an 1
+ an x + C .
n +1
n
2

, -
( n ) - (
n +1 ).
) A

1- ( x a ) k

dx, A, a,

k =1
A

x a dx = A x a dx = A ln x a + C.
k 2 .
A
( x a)
k
( x a ) k dx = A ( x a ) dx = A k +1

k +1

+C =

A
+ C.
(1 k )( x a ) k 1

) 2- :
,

p2
q < 0.
4

(x

Mx + N
2

+ px + q

dx,

M , N , p, q,

l =1 .

pM

M
+N

( 2 x + p ) N pM

2
2
2 dx =
dx = 22
+
x 2 + px + q
x + px + q x 2 + px + q

M
2x + p
pM
1

=
dx + N
dx.

2 x 2 + px + q
2 x 2 + px + q

Mx + N
x 2 + px + q dx =

( 2x + p) M

2x + p

: x 2 + px + q dx = J *

x 2 + px + q dx = J1.
15

M +N
M
pM

x 2 +x px + q dx = 2 J + N 2 J1.

p2
q < 0,
4

J = ln x 2 + px + q

2x + p
x 2 + px + q
2
dx
=
x 2 + px + q dx = ln x + px + q + C.
x 2 + px + q

J =

x 2 + px + q > 0

x .

+ C.

1
1
dx =
dx
2
x + px + q
p
p2
.

x + +q
2
4

J1 =

p
: x + = t , dx = dt J1 =
2

a 2 = q

1
dt ,
t + a2

p2
> 0.
4


x+

1
t
1
J1 = arctg + C = arctg
a
a
a
Mx + N

, x 2 + px + q dx =

p
2 +C =

2
4q p 2

arctg

2x + p
4q p 2

M
2 N pM
2x + p
ln x 2 + px + q +
arctg
+ C.
2
2
4q p
4q p 2

e 2 .
Mx + N

M
2

( 2 x + p ) dx

( x 2 + px + q )l + N

(x

(x

2x + p
2

+ px + q

Mx + N
2

+ px + q

pM

+N

2
2
dx =
l
x 2 + px + q

( 2x + p) M

( x 2 + px + q )l dx =

J =

dx =

(x

pM
dx
2
2 x + px + q

dx = J

+ px + q

( x 2 + p + q )l dx = J l .

M
pM

J + N
2
2

2x + p
2

+ C.

dx .

16

J l .


J =

J =

( 2 x + p ) dx = dt .

dt
t l +1
1
=
+C =
+ C.
l
l +1
(1 l ) t l 1
t
1

(1 l ) ( x 2 + px + q )
Jl =

x 2 + px + q = t .

(x

+ C.

l 1

1
2

+ px + q

dx =

1
l

x + p + q p

2
4

dx

.
2

p
p
x + = t q = a 2 ,
2

Jl =

(t

1
2

+ a2

dt

, I e
J l 1 =

(t

1
2

+ a2

dx.

l 1

:
Jl =

(t

1
2

+ a2

1
1
= 2
2

a t + a2

Jl =

dt =

l 1

1
a2

(t

+ a2 t 2

(t 2 + a 2 ) l

dt

(t

t2
2

+ a2

dt =

1
a2

1
t 2 + a 2

(t

t2
2

+ a2

dt =

(*)

(t

t2

dt

1
t2
J

dt

2 l 1
l

a
t 2 + a2

dt
l 1

+a

2 l

dt = t

(t

t
2

+ a2

dt.

.
u = t ,

dv =
1

(t

t
2

+a

2 l

dt =

1 d t 2 + a2
.
2 t 2 + a2 l

du = dt , v = 2 (1 l )(t 2 + a 2 ) l 1 .

17

t2

(t 2 + a 2 )l dt = 2 (1 l )(t 2 + a 2 )l 1 2(1 l ) (t 2 + a 2 )l 1 dt

,
t2

(t 2 + a 2 )l dt = 2 (1 l ) (t 2 + a 2 )l 1 2(1 l ) J l 1 .
(*), :
Jl =

1
a2

t
J 1
l 1 2 (1 l ) t 2 + a 2

1
2( l 1) a 2

l 1

t 2 + a2

Jl =

l 1

1
J l 1

2(1 l )

+ ( 2l 3) J l 1 .

I e I e 1 ,
I l 2 ,
J1 =
, e 2

(x

Mx + N
2

+ px + q

dx =

1
1
t
dt = arctg + C .
2
a
a
t +a
2

M
1
2
2 (1 l ) x + px + q

l 1

pM

+N
J l ,
2

I l

. I l
p
x , x + = t.
2

(x

3x + 2
2

+ 6 x +14

dx .

-
2- ,

p2
36
q =
14 = 5 < 0
4
4

18

( 2 x + 6) 3 + 2 9

3x + 2

( x 2 + 6 x +14)3 dx = ( x 2 + 6 x2+14)3

dx =

3
2x + 6
1
dx 7
dx =

3
3
2
2
2 x + 6 x + 14
x + 6 x + 14

3 x 2 + 6 x + 14
1
=
dx 7
dx =
3
3
2 x 2 + 6 x + 14
( x + 3) 2 + 5
3
1
1
=
7
dx.
2
3
2
4 x + 6 x + 14
( x + 3) 2 + 5

(
(
(

)
)
)

(( x + 3 )

(**)

+5

dx =

(t

1
2

+5

dt,

,
J3 =

(t

1
2

+5

dt =

t = x + 3 .
l = 3,

a2 = 5 :

1
t
t
3
=
+
3

J
+
J 2.
2
2
2
2
2

2 2 5 t + 5
20
20 t + 5

I 2 ,
l = 2,

a2 = 5 :

J2 =

(t

1
2

+5

dt =

1 t
t
1

+ J1 =
+ J1.
2
2
2 1 5 t + 5
10 t + 5 10

I 2 , :
J3 =

20 t + 5

3
t
1

+ J1
2
20 10 t + 5 10

3t
3
+
J1 ,
2
200 t + 5 200

J3 =

20 t + 5

J1 =

1
1
t
dt =
arctg
+ C.
t +5
5
5
2

,
J3 =

( ( x + 3)

+5

dx =

t
2

20 t + 5

3t
3
t
+
arctg
+ C.
2
200 t + 5 200 5
5

x , :

19

3( x + 3)

x+3

( x 2 + 6 x + 14)3 dx = 20( x 2 + 6 x + 14) 2 + 200( x 2 + 6 x + 14) + 200

arctg

x+3
+ C.
5

(**) , .
10.
. u

u k vl ,

k = 0,1,2, , e = 0,1,2, .

. u v

().
1
. 3u 6v 2 + u 3v 2u + 2v + 12.
2

-
.
. u

:
R( u, v ) =

P( u , v )
Q( u, v )

P (u , v )

Q(u , v )

. R( u, v ) =

2u 3v 5 3uv 4 + 2v
u 5v + 2v 6 + 4

. R( u , v ) u v ,

u v

t : u = R1 ( t ) ,

v = R2 ( t ) , R ( R1 ( t ) , R2 ( t ) )

.
. u = R1 ( t ) v = R2 ( t )
t . u v
P(u, v )

Q(u , v )

P( ( R1 ( t ) , R2 ( t ) ) = R3 ( t ) Q( ( R1 ( t ) , R2 ( t ) = R4 ( t ) ) .
20

, R( R1 ( t ),R2 ( t ) ) =

R3 ( t )
R4 ( t )

.
11.

ax +b
cx +k

n
1) R
x,

dx.


R( u, v ) ,

u = x ,

v =n

ax + b
cx + k

x ,

n = 2,3, .

n
. R
x,

ax +b
cx +k

dx


t .
:
: x =

ax + b
=t ,
cx + k

ax + b
= t n.
cx + k

kt n b
= R1 ( t )
a ct n

dx =

( ak bc ) nt n 1 dt

(a ct )

n 2

t.

( ak bc ) nt n 1 = R ( t )
2

t
n 2

(a ct )

(, ak bc 0 ), dx = R2 ( t ) dt
,

R x, n

ax + b
dx = R ( R1 ( t ), t ) R2 ( t ) dt .
cx + k

R( R1 ( t ) t ) R2 ( t )

t
R3 ( t ) .

21

, R x, n

ax + b
dx = R3 ( t ) dt .
cx + k

2) R (x,

ax 2 +bx +c dx


R( u, v ) ,

u = x ,

v = ax 2 + bx + c

x.
. R (x,

ax 2 +bx + c dx


t .

ax 2 + bx + c

x1 , x2 ,

ax 2 + bx + c = a( x x1 ) ( x x2 )

x x2
x x2

R x, ax 2 + bx + c = R x, ( x x1 ) a
= R1 x,

x
x

x
1
1

1.
,

ax 2 + bx + c

a > 0 .
:

ax 2 + bx + c = t x a

a > 0 ,

ax 2 +bx + c = t 2 2 x a t + ax 2 ,

t .
R (x,

ax 2 + bx + c = t

t2 c
a
2t a + b

x=

t2 c
2t a + b

ax 2 + bx + c 0 ).

t .

ax 2 +bx +c dx = R1 ( t )dt.

a < 0,

c > 0 ( ax 2 + bx + c 0 ),

ax 2 + bx + c = xt + c .

x 2 +a 2 dx.

22

x2 + a2

t = x 2 + a 2 + x, x 2 + a 2 = t 2 2tx + x 2 , x =

t 2 a2
2t

x2 + a2 = t x =

t 2 + a2
2t

t 4 a4
2t 2t t 2 a 2 2
t 2 + a2
,dx =
dt =
dt.
x x + a =
4t 2
4t 2
2t 2
2

x 2 + a 2 dx =

t 2 + a2 t 2 + a2
1 2a 2 a 4
a2
t 2 a4

dt
=
t
+
+
dt
=
ln
t
+

+C =
2t
4
t
2
8 8t 2
2t 2
t 3

a2
t 4 a4
a2
x
ln t +
+
C
=
ln x + x 2 + a 2 +
x 2 + a 2 + C.
2
2
2
2
8t

12. R(sin x,cos x ) dx.


. R(sin x,cos x ) dx
x
t = tg < x < , ,
2

t .

t = tg

x x
, = arctgt,
2 2

x = 2arctg t,

2
dx =
dt .
1 +t 2

x
sin x, cos x tg = t:
2

x
x
x
2 sin cos
2tg
x
x
2
2 =
2 = 2t ,
sin x = 2 sin cos =
2
2 sin 2 x + cos 2 x 1 + tg 2 x 1 + t 2
2
2
2
x
x
x
cos 2 sin 2
1 tg 2
2
x
x
2
2=
2 = 1 t .
cos x = cos 2 sin 2 =
2
2 sin 2 x + cos 2 x 1 + tg 2 x 1 + t 2
2
2
2
2t

1 t 2 2dt

,
= R1 ( t )dt ,
R( sin x,cos x )dx = R
1 + t 2 1 + t 2 1 + t 2

t .
dx

. sin x .
23

R1 ( t )

x
tg .
2

dx
1+t 2
2
dt
x
=
sin x 2t 1 + t 2 dt = t =ln t + C = ln tg 2 + C.

R( sin x, cos x ) ,

.
,
.
1)
sin x = t ,

cos xdx = dt

R(sin x ) cos xdx,

R(t )dt .

2) R(cos x ) sin xdx,


cos x = t ,

sin xdx = dt .

sin 3 xdx

.
.
2 + cos x

cos x = t , sin xdx = dt :


sin 3 xdx
sin 2 x sin x
1 t 2
t 2 1
3

=
dx
=
(

dt
)
=
2 + cos x 2 + cos x
2 +t
t + 2 dt = t 2 + t + 2 dt
=

t2
cos 2 x
2t + 3 ln t + 2 + C =
2 cos x + 3 ln cos x + 2 + C.
2
2

3) tgx ,
tgx = t ,

x = arctgt , dx = dt 2
1+ t

: R( tgx ) dx = R( t )


dt
.
1 +t 2

4)
tgx = t ,
tgx :

cos 2 x =

R sin 2 x,cos 2 x ,

sin 2 x, cos 2 x

1
1
tg 2 x
t2
dt
2
=
,
sin
x
=
=
, dx =
.
2
2
2
2
1 + tg x 1 + t
1 + tg x 1 + t
1+t2

.
24

dx

.
.
2 sin 2 x

tgx = t :
dx

2 sin 2 x =

dt

t
2
1+ t2
2
1+ t

dt
1
t
1
tgx
=
arctg
+C =
arctg
+ C.
2
2+t
2
2
2
2

5) sin m x cos n xdx, m n .


.
) m n , ,
, n .

sin

n = 2 p +1

x cos 2 p +1 xdx =sin m x cos 2 p x cos xdx =sin m x 1 sin 2 x

cos xdx.

sin x = t , cos xdx = dt ,


t .
.

cos 3 x
sin 4 x dx.

sin x = t , cos xdx = dt , :

cos 3 xdx
1 sin 2 x cos xdx
1 t 2 dt
=
=
sin 4 x
t4 =
sin 4 x
dt
dt
1 1
1
1
= 4 2 = 3 + + C =
+
+C
3
t
t
t
3t
3 sin x sin x

) m n ,
n = 2q

m =2p,

,
sin 2 x =

1 cos 2 x
1 + cos 2 x
, cos 2 x =
,
2
2

1 1
1 1

2p
2q
sin x cos xdx = 2 2 cos 2 x 2 + 2 cos 2 x dx.

, ,
cos 2 x .

25

, )
1 + cos 2 x
.
cos 2 x =
2

, cos kxdx, .
. sin 4 xdx.

1
(1 cos 2 x ) 2 dx = 1 1 2 cos 2 x + cos 2 2 x dx =

4
4
1
1
sin 4 x
13
= x sin 2 x + (1 + cos 4 x ) dx = x sin 2 x +
+ C.
4
2
4
2
8

sin

xdx =

) m n ,
, tgx = t ( 4)
6)

cos mx cos nxdx, sin mx cos nxdx, sin mx sin nxdx.


m n :
cos mx cos nx =

1
( cos( m + n ) x + cos( m n ) x ),
2

sin mx cos nx =

1
( sin ( m + n ) x + sin ( m n ) x ),
2

sin mx sin nx =

1
( cos( m + n ) x + cos( m n ) x ).
2

. sin 5 x sin 3 xdx.


1

sin 5 x sin 3xdx = 2 ( cos 8 x + cos 2 x ) dx =

sin 8 x sin 2 x
+
+ C.
16
4

13.
1. ( , )
)

1 + x3
x dx ;

) (3

x 3 x

dx

2 x + 3 x
2x ,
)
5x

(1 + 2 )

x +1 2

2
) 1 1 +2 x dx ;

1+ x

26

dx ;

) tg 2 xdx ;
2
) 1 21 x dx ;

x 1

1 1 + x 2
1 + x 2

dx ;

x 1 x2
1 x 2

dx .

2. ( , )
) (3

x +1 x +1 dx ;

) ( x +sin x )2 dx, (

x +cos

x 1
dx ;
x +1

) (1 e

) dx ;
3

x
dx .
1 + x2

) ln

dx ;

3.( )
P( x ) = x 2 ( a +b ) x + ab = 0,Q( x ) = x 2 2ax + a 2 +b 2 .
:
)

1
P( x ) dx ,

1
Q( x ) dx

P( x )
Q( x ) dx ,

( P( x ) ) 2 dx
)
( Q( x ) ) 2

,
Q( x )

) P 2 ( x ) dx ,

) P ( x 2 ) dx ,

) Q ( x 2 ) dx .

4. ( )
sin 2 x

) ab sin 2 x ( a + b ) sin x +1 dx ,

) a sin x + b cos x dx ,
sin 2ax

) ab cos 2 ax + ( a + b ) cos ax + 1 dx ,

) cos ax

) sin ax ln( b + cos ax )dx ,

) sin ax cos bxdx ,

) sin 4 axdx .

5. P( x )

Q( x )

1 +sin ax dx ,

sin 2 ax + b sin 2ax + a


a sin 2 ax + b cos 2 ax dx ,

(. 3).

) e x P (x )dx , ) xP (e x )dx , ) xP(sin x )dx ,

P (

x ln xdx ,

x ln P ( x )dx ,

) P (ln x )dx .

27

3-5 a b .
3.
3. P( x ) = x 2 x 2, Q( x ) = x 2 +7 x +16.
1

a) P( x ) dx = x 2 x 2dx.

D = 9 > 0.

x1 = 1, x2 = 2 . ,

x 2 x 2 = ( x +1)( x 2 ) .

1 :
1
A
B
=
+
.
x x 2 x +1 x 2
2

,
:
A( x 2 ) + B( x + 1) = 1 .

x . x = 2 ,
: 3B = 1

B=

1
.
3

x = 1 , 3 A = 1

A=

1
.
3

1
1
1
,
= 3 + 3 .
2
x x 2 x +1 x 2

dx

dx

dx

x 2 x 2 = 3 x 2 x +1 = 3 ( ln x 2 ln x +1 ) + C = 3 ln
)

x 2
+ C.
x +1

1
1
dx = 2
dx.
Q( x )
x + 7 x +16

Q( x ) : D = 15 < 0 .
.
:

7 15

x 2 + 7 x + 16 = x + + .
2
4

28

Q( x ) dx =

7 15
x + +
2
4

dx

7
: x + = t. dx = dt .
2

1
t2 +

15
4

1
t
2
2t
arctg
+C =
arctg
+ C.
15
15
15
15
4
4

dt =

x ,
1

Q( x ) dx = x 2 + 7 x + 16 dx =
P( x )
) Q( x ) dx =

(x

x 2 x 2
2

+ 7 x +16

2
2x + 7
arctg
+ C.
15
15

dx =

x 2 x 2
dx.
2 x +7

.
:
55
x2 x 2 1
9
= x + 4
2x + 7
2
4 2x + 7

:
P( x )

Q( x ) dx =
=

x2 x 2
9 55 1
1
dx = x +
dx =
2x + 7
4 4 2x + 7
2

1
9
55
dx
x2 9
55
xdx

dx
+
=
x+
ln 2 x + 7 + C.

2
4
4 2x + 7
4 4
8

( P( x ) ) 2 dx = J .
)
( Q( x ) ) 2
P( x ) = 2 x 1,Q( x ) = 2 x + 7
( 2 x 1) 2
4x2 4x +1

J =
dx
=
4 x 2 + 28 x + 49 dx.
2
( 2x + 7)

- ,
:
29


32 x + 48
2x + 3
dx = x 16
J = 1
dx.
2
( 2x + 7)2
( 2x + 7)


- 1- :
2x + 3
A
B
=
+
.
2
( 2x + 7) 2x + 7 ( 2x + 7) 2

:
2x + 3
1
4
=

.
2
( 2x + 7) 2x + 7 ( 2x + 7) 2

1
1
32
J = x 16
dx 4
dx = x 8 ln 2 x + 7
+ C.
2
2
x
+
7
2
x
+7
( 2x + 7)

Q( x )
x 2 + 7 x +16
x 2 + 7 x +16
dx
=
dx
=
) P 2 ( x )
x2 x 2 2
( x 2 ) 2 ( x +1) 2 dx

:
x 2 + 7 x + 16
A
B
C
D
=
+
+
+
2
2
2
2
( x 2 ) ( x + 1) ( x 2 ) x 2 ( x + 1) x + 1

A( x + 1) 2 + B( x + 1) 2 ( x 2 ) + C ( x 2 ) 2 + D( x + 1)( x 2 ) 2 = x 2 + 7 x + 16.

x = 1 : 9C = 10
A=

C=

10
.
9

x = 2 9 A = 34

34
.
9

, , x = 0 x =1 :
A 2 B + 4C + 4 D = 16

4 A 4 B + C + 2 D = 24

, :

30

35

B 2D = 9

35
2 B D =
9

B =

35
27

D=

35
27

,
34
Q( x )
x 2 +7 x +16
1
35 1
10
1
35 1
dx
=
dx =
P2 ( x)
2
2
9 ( x 2 ) 2 27 x 2 + 9 ( x +1) 2 + 27 x +1
dx =
x x 2

34 1
10 1
35
x +1
=

+
ln
+C
9 x 2
9 x +1 27
x 2

) P( x 2 ) dx = x 4 x 2 2 dx

x4 x2 2 = 0 .

x 2 = 2 , x 2 = 1 .

) (

)(

)(

)(

x4 x2 2 = x2 2 x2 +1 = x + 2 x 2 x2 +1

1
dx
2 x 2 x 2 +1

P( x 2 ) dx = ( x +

)(

)(


- 1- 2-

1
A
B
Mx + N
=
+
+ 2
2
x + 2 x 2 x +1 x + 2 x 2
x +1

)(

)(

)(

x = 2

)(

A x 2 x 2 + 1 + B x + 2 x 2 + 1 + ( Mx + N ) x 2 2 = 1 ,

B = 1 B =

1
6 2

6 2

, x = 0 :

A = 1 A =

2 A + 2 B 2 N =1;

1
N = .
3

31

1
6 2

x= 2

6 2

A B,

x =1 :

(1 2 )2 A + (1 + 2 )2 B M N = 0;

A, B, N

M =0

P( x 2 ) dx = 6

1
1
1
1 1
1
x 2
1
+

ln
arctgx + C
dx =
3
2 x + 2 6 2 x 2 3 x 2 +1
6 2
x+ 2

) Q ( x 2 ) dx = x 4 + 7 x 2 +16 dx

x 4 + 7 x 2 + 16 = 0

x 4 + 7 x 2 + 16

. :

)(

x 4 + 7 x 2 + 16 = x 2 + 4 x 2 = x 2 x + 4 x 2 + x + 4

).

Q( x 2 ) dx = ( x 2 x + 4)( x 2 + x + 4) dx

2- :

1
M x + N1 M 2 x + N 2
= 21
+
.
2
x x + 4 x + x + 4 x x + 4 x2 + x + 4
2

)(

( M 1 x + N1 ) ( x 2 + x + 4 ) + ( M 2 x + N 2 ) ( x 2 x + 4 ) = 1
, :

( M 1 + M 2 ) x 3 + ( N1 + M 1 + N 2 M 2 ) x 2 + ( N1 N 2 + 4M 1 + 4M 2 ) x + 4 N1 + 4 N 2 = 1
:
M1 + M 2 = 0
N + M + N M = 0
1
1
2
2

N1 N 2 + 4M 1 + 4 M 2 = 0
4 N1 + 4 N 2 = 1

32

1
1
1
1
M 1 = , N1 = , M 2 = , N 2 = .
8
8
8
8

x 1

x +1

Q( x 2 ) dx = 8 x 2 x + 4 dx + 8 x 2 + x + 4 dx
J1 =
J1 =

x 1
dx J 2 =
x x +4
2

x +1
x 2 + x + 4 dx.

1
2 x 2
1 ( 2 x 1) 1
1
2 x 1
1

dx = 2
dx = 2
dx 2
=
2 x2 x +4
2 x x +4
2 x x +4
x x +4

1
1
2
2 x 1
1

2
= ln x x + 4
dx = ln x 2 x + 4
arctg
+C
2
2
2
15
15

1
15

x +

2
4

,
J2 =

1
2
2 x +1
2
arctg
+C
ln x + x + 4 +
2
15
15

Q( x 2 ) dx = 8 ln( x
1

x+4

2
2 x 1
arctg
+
15
15

1
2
2x +1
+ ln x 2 + x + 4 +
arctg
+C =
8
15
15
1 x2 + x + 4
1
2 x 1
2x +1
= ln 2
+
+ arctg
arctg
+ C.
8 x x + 4 4 15
15
15

1. .. ./ ..
, .. . .: , 1998.
2. .. . .:
, 1995.
3. .. . .1. .:
, 2000.
33

1.

2.

3.

4.

5.

6.

7.

8.

12

9.

15

10.

22

11.

23

12.

R (sin x,cos x ) dx.

23

13.

30

38

34

020815 20.09.93

6084 1/16 .-..2,5

150 .
-
.
. 173003, , .. -, 41.

35